How infected women in Fortaleza-CE cope with AIDS - Carvalho, Carolina Maria de Lima; Galvão, Marli Teresinha Gimeniz (Revista da Escola de Enfermagem da USP, 2008)
The objective of this study was to learn how women with Aids cope with daily living after receiving their diagnosis. It is an exploratory, descriptive study with a qualitative approach based on thematic oral history for data collection and analysis. Ten women with Aids were interviewed at a reference hospital in Fortaleza, State of Ceará, from December 2004 to March 2005. A semi-structured questionnaire was used for data collection. The results revealed different ways of coping, related to the fragility of the discovery of the diagnosis, to the need to hide the infection due to the discrimination and prejudice faced by the victims, and to the constant perception of death. In addition, the women expressed feelings such as shame, concern about family, abandonment, solitude, sadness, fear and anxiety. The authors conclude that, two decades after the epidemic broke out, women still face evident difficulties when they experience their infection.